Tackling the Scalability Challenge in Plasmonics by Wrinkle-Assisted Colloidal Self-Assembly - Yu, Ye; Ng, Charlene; Koenig, Tobias A. F.; Fery, Andreas (Langmuir, 2019)
Electromagnetic radiation of a certain frequency can excite the collective oscillation of the free electrons in metallic nanostructures using localized surface plasmon resonances (LSPRs), and this phenomenon can be used for a variety of optical and electronic functionalities. However, nanostructure design over a large area using controlled LSPR features is challenging and requires high accuracy. In this article, we offer an overview of the efforts made by our group to implement a wrinkle-assisted colloidal particle assembly method to approach this challenge from a different angle. First, we introduce the controlled wrinkling process and discuss the underlying theoretical framework. We then set out how the wrinkled surfaces are utilized to guide the self-assembly of colloidal nanoparticles of various surface chemistry, size, and shape. Subsequently, template-assisted colloidal self-assembly mechanisms and a general guide for particle assembly beyond plasmonics will be presented. In addition, we also discuss the collective plasmonic behavior in depth, including strong plasmonic coupling due to nanoscale gap size as well as magnetic mode excitation and demonstrate the potential applications of wrinkle-assisted colloidal particle assembly method in the field of mechanoresponsive metasurfaces and surface-enhanced spectroscopy. Lastly, a general perspective in the field of template-assisted colloidal assembly with regard to potential applications in plasmonic photocatalysis, solar cells, optoelectronics, and sensing devices is provided.
CRIS-Team Scopus Importer:2022-04-14